Assessing Household's Solid Waste Segregation Behavior in the City of Nepal: A Structural Equation Modeling Approach (Quest Journal of Management and Social Sciences, 2025)
Background: In the context of rapid urbanization and rising municipal solid waste generation, solid waste segregation is crucial for effective management; however, poorly researched behavioral issues in the developing world, including Nepal, hinder its implementation.Purpose: This research examines the psychological, social, and ethical drivers of household waste-segregation behavior in Itahari Sub-Metropolitan City, utilizing a combined framework that integrates the Extended Theory of Planned Behavior (ETPB) and the Norm Activation Model (NAM).Design/methodology/approach: A cross-sectional survey was conducted, in which 502 households were chosen by using stratified random sampling from urban and semi-urban wards. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, using SmartPLS4, was employed to analyze both measurement and structural models.  Findings: Based on its findings, it has been observed that behavioral attitude, subjective norms, perceived control over behavior, moral obligation, and moral obligation judgment play a critical role in determining the willingness to segregate waste, which, in turn, significantly influences the observability of segregation behavior. Knowledge of environmental outcomes has no substantive effect on intention. It does not have a positive impact on behavior, but a weak yet significant negative relationship with practice indicates the existence of an awareness-behavior gap. These findings underscore the importance of developing moral responsibility, social norms, and perceived self-efficacy rather than relying solely on awareness-based interventions.Conclusion: The paper thus concludes that sustainable household waste segregation behavior in Nepal can be promoted through culture-based, psychologically informed, and infrastructure-based initiatives that extend beyond typical educational campaigns.Keywords: Solid waste, Segregation, Intention Behavior, PLS-SEM